A Correlation Between Education And Family Support With Regular Control Of Blood Sugar Levels In Diabetes Mellitus Patients At Hasanudin Damrah Manna Hospital - Meriyansyah, Meriyansyah; Darmawansyah, Darmawansyah; Fauzi, Yusran (Journal of International Public Health, 2024)
WHO predicts an increase in the number of DM patients in Indonesia to around 21.3 million in 2030. Indonesia is ranked fourth in the world for the number of DM sufferers. The Basic Health Research Report in 2018 had the 2nd highest mortality aged 45-54 year group at 14.7%. Data from Hasanudin Damrah Hospital, the number of DM sufferers in 2021 was 902 cases, in 2022 there were 602 and in 2023 from January to June there were 497. Data from health workers at Hasanudin Damrah Hospital said that many DM sufferers did not check their blood sugar levels. The aim of the research is to determine a correlation between education and family support and regular control of blood sugar levels in Diabetes Mellitus sufferers at Hasanudin Damrah Manna Hospital. This research is a quantitative research using a cross sectional study design. The number of samples in the study was 69 respondents. The analysis used is univariate and bivariate analysis with the chi-square test. The results of the research were that most of the respondents had a secondary education level, 41 respondents (59.4%), most of the respondents did not have family support, 37 respondents (53.6%), some of the respondents had irregular control of blood sugar levels, 38 respondents (55.1%). There is a significant correlation between education (0.000) and family support (0.004) with regular control of blood sugar levels at Hasanudin Damrah Manna Hospital. It is hoped that further research can be carried out to look at the aspect of external support for regular control of blood sugar levels in DM sufferers.